2017
DOI: 10.1111/and.12770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kaempferia parviflora on sexual performance in streptozotocin-induced diabetic male rats

Abstract: SummaryKaempferia parviflora Wall. Ex.Baker or Krachidum (KP) has been used locally in medicine and food. It has been claimed that KP has aphrodisia properties; however, no scientific data in support of this function in diabetic model have been reported. This study aimed to investigate the efficacy of KP on sexual behaviour and sperm parameter in streptozotocin (STZ)-induced diabetic male rats. Diabetes was induced in twenty male rats by STZ and divided into four groups: diabetic control group, and 3 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
2
37
2
2
Order By: Relevance
“…To further investigate the aphrodisia property of KP, male rats models are established with streptozotocin (STZ)-induced diabetes, which is associated with the complication of sexual dysfunction. KP treatment significantly elevates the levels of serum testosterone, the concentration of sperm, and the weight of testes and improves the behavior of copulation in STZ-induced diabetic rats [39] (Table 1). Similar effects of KP extract in aging rats on enhancement of sexual activity, which might be associated with increased dopaminergic function in hypothalamus.…”
Section: Sexual Enhancing Activitymentioning
confidence: 99%
“…To further investigate the aphrodisia property of KP, male rats models are established with streptozotocin (STZ)-induced diabetes, which is associated with the complication of sexual dysfunction. KP treatment significantly elevates the levels of serum testosterone, the concentration of sperm, and the weight of testes and improves the behavior of copulation in STZ-induced diabetic rats [39] (Table 1). Similar effects of KP extract in aging rats on enhancement of sexual activity, which might be associated with increased dopaminergic function in hypothalamus.…”
Section: Sexual Enhancing Activitymentioning
confidence: 99%
“…Kaempferia parviflora Wall ex Baker, commonly known as black galingale or 'Krachai Dam' in Thai, is a native Thai plant of the Zingiberaceae family and its rhizomes have been widely used in traditional medicine as a health-promoting herb for treating a variety of ailments with benefits including anti-mycobacterial effects (Yenjai et al, 2004), sexual dysfunction and ulcer treatment (Rujjanawate et al, 2005), anti-allergy (Tewtrakul et al, 2007), anti-flatulence and anti-dysentery (Chomchalow et al, 2003), antidepressant (Hawiset et al, 2011) and increasing blood flow to the testes (Chaturapanich et al, 2008;Tewtrakul and Subhadhirasakul, 2008). Krachai Dam exhibited aphrodisiac properties that improved the sperm density, testosterone level and sexual performance of streptozotocin-induced diabetic rats (Fungfueng et al, 2016;Lert-Amornpat et al, 2017). Gabriely et al (2002) reported that reduced visceral fat content could prevent insulin resistance and glucose intolerance in diabetic fatty rats.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnopharmacologically, the plant rhizomes have been traditionally used in folk medicine for centuries for longevity promotion, anti-fatigue, appetite induction, male sexual stimulation, anti-stomachache, and laxative [2][3]. KP extract and its major constituents have been reported to confer several health beneficial effects through in vitro and animal studies, including aphrodisiac activity [4][5][6][7], anti-inflammation [8], anti-cancer [9][10] , cardioprotection [11][12], anti-peptic ulcer [13], antimicrobial [14], anti-allergy [15], anti-mutagenicity [16], anti-depression [17], anti-cholinesterase activity [17][18], prevention of the brain from valproic acid-induced the impairments of spatial memory [19], inhibition of intrinsic aging process [20], anti-osteoporosis [21], reduction of pain threshold and severity of osteoarthritis [22], anti-obesity and preventing obesity-induced dermatopathy [23][24], inhibition of fat accumulation and muscle atrophy [25], increased whole-body energy expenditure [26] and promotion of the differentiation of brown adipose tissue [27][28]. In terms of antidiabetic activity, the ethanol extract of K. parviflora was reported to decrease blood glucose in streptozocin-induced diabetic rats [29].…”
Section: Introductionmentioning
confidence: 99%